Involving seniors in designing information architecture for the web - Kurniawan, Sri Hastuti; Zaphiris, Panayiotis; Ellis, R. Darin (My University, 2001)
The present study utilized the card sorting technique and cluster analysis to define the best information architecture of Web health information for seniors. Sixteen seniors participated in the card sorting, twenty in the category identification and thirteen in category labeling experiments. Seniors participated in the study tend to group the tested items conceptually at the higher level but tend to group the items based on common words found in the titles at the lower level of the hierarchy. The study also found that user grouping produced more heterogeneous structure than the Dmoz set-up information architecture. Category labels suggested by seniors were observed to be less formal than the Dmoz category labels.